Can Tax‐Loss Selling Explain the January Seasonal in Stock Returns? - CHAN, K. C. (Journal of Finance, 1986)
ABSTRACT This paper analyzes the tax‐loss selling hypothesis as an explanation of the January seasonal in stock returns and argues that rational tax‐loss selling implies little relation between the January seasonal and the long‐term loss. Empirical results show that the January seasonal is as strongly related to the long‐term loss as it is to the short‐term loss. The evidence is inconsistent with a model that explains the January seasonal by optimal tax trading.